1982
DOI: 10.1111/j.1600-065x.1982.tb01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Cell Surface Interaction Structures Detected Using Cytolysis‐Inhibiting Monoclonal Antibodies

Abstract: We screened monoclonal antibodies obtained by xenogeneic immunization for their capacity to inhibit T cell-mediated cytolysis. These antibodies fell into two classes according to the cell structures they recognized, of 30-35 K and 94-180 K apparent molecular weight, respectively. The main features of these structures and of their interaction with the corresponding antibodies were reviewed. The inhibition of cytolysis by these antibodies was shown to occur mainly at the effector cell level, at the recognition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(58 citation statements)
references
References 116 publications
1
57
0
Order By: Relevance
“…2B, the immunoaffinity purified mCD8␣␤-LZ material is ϳ90% pure. The 2H11 mAb-purified mCD8␣␤-LZ protein expresses the native epitopes recognized by five distinct anti-CD8␣ mAbs (53.6.72, 19/178, H59 -101.7, YTS105, and YTS169) (34,35,39) and four anti-CD8␤ mAbs (53.5.8, H35-17, YTS156.7, and KT112) (34,35,39,40), as measured by BIAcore binding studies (data not shown).…”
Section: Design Of Secretedmentioning
confidence: 99%
“…2B, the immunoaffinity purified mCD8␣␤-LZ material is ϳ90% pure. The 2H11 mAb-purified mCD8␣␤-LZ protein expresses the native epitopes recognized by five distinct anti-CD8␣ mAbs (53.6.72, 19/178, H59 -101.7, YTS105, and YTS169) (34,35,39) and four anti-CD8␤ mAbs (53.5.8, H35-17, YTS156.7, and KT112) (34,35,39,40), as measured by BIAcore binding studies (data not shown).…”
Section: Design Of Secretedmentioning
confidence: 99%
“…Effector cells (107 cells/ml) were incubated for 1 h at 4 °C in R2 medium (R5 medium with 2 % FCS) containing 10 gg/ml of rat MAbs GK1.5 (Dialynas et al, 1983) or H35.17.2 (Golstein et al, 1982). They were then washed twice with cold R2 medium, resuspended in cold R0 medium containing 108 sheep anti-rat lgG dynabeads/ml (Dynal) and further incubated for 1 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…2A). The results clearly indicate that the CD8 ϩ T-cell fraction recognizes the VP1 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] , VP3 151-170 , and VP3 [171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] peptides. As expected, the CD4 ϩ T-cell fraction produced IFN-␥ in response to known Th epitope-containing peptides, VP1 231-250 and VP3 [21][22][23][24][25][26][27][28][29][30][31][32][33][34]<...>…”
Section: Identification Of 20-mer Peptides Capable Of Stimulating Ifnmentioning
confidence: 99%
“…Figure 1 represents a typical profile of the consistent pattern of IFN-␥ production by CNS-IL at an early stage (7 to 10 days) of TMEV infection. Interestingly, the VP3 151-170 , VP3 [171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] , and VP1 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] peptides stimulated noticeably higher numbers of IFN-␥-producing cells than the VP2 71-90 , VP3 [21][22][23][24][25][26][27][28][29][30][31][32]…”
Section: Identification Of 20-mer Peptides Capable Of Stimulating Ifnmentioning
confidence: 99%
See 1 more Smart Citation